Occupational asthma after inhalation of dust of the proteolytic enzyme, papain. - Milne, J (1975)
Papain is a proteolytic enzyme widely used by biochemists. In experiments on animals papain has been shown to cause emphysema either when they inhaled a single small dose or after intratracheal inhalation. Four food technologists were occupationally exposed to heavy concentrations of papain dust in air. Subjects 1 and 2 developed an immediate acute asthmatic reaction, and symptoms of obstructive airways disease persisted for some months while each remained in the same working area, presumably exposed to small gradually diminishing amounts of residual papain dust. Tests of respiratory function were carried out on all four subjects 1 1/2 years later and showed in subjects 1 and 3 minimal abnormality of bronchial reactivity and of ventilation distribution. Review of the literature reveals only two reports of asthma resulting from papain inhalation, although its antigenic and skin sensitizing qualities have been known and described for many years. It seems remarkable that a substance such as papain, shown to be a potent cause of lung damage in experimental animals, should have produced so little evidence of abnormality in our subjects after considerable exposure. Follow-up ventilatory function tests may cast further light on this but we postulate that the asthmatic response may be biologically protective and those lacking this reaction could later develop emphysema as a long-term outcome.